Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan: Studi Kasus Pada Toko HP IVAN CELL Kediri - Andung Kahuripan (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This study aims to determine the Effect of Service Quality and Customer Satisfaction on Customer Loyalty (Case Study at HP IVAN CELL Store Kediri). The variables of this research are Service Quality (X1), Customer Satisfaction (X2) and Customer Loyalty (Y). This study uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. While the analysis used is, multiple linear regression test. Sampling in this study used purposive sampling with consideration of all consumers of HP IVAN CELL Kediri Store, totaling 86 people. The results of this study using the SPSS 22.0 program using a significant level of 5% or 0.05 with the results (1) partially service quality has a significant effect on customer loyalty with a significant value of 0.000 <0.05, which means Ha1 is accepted and. (2) partially customer satisfaction has a significant effect on customer loyalty with a significant value of 0.000 <0.05, which means Ha2 is accepted. (3) Simultaneously Service Quality and Customer Satisfaction have a significant effect on Customer Loyalty, a significant value of 0.000 <0.05, which means Ha3 is accepted.